29.5k views
0 votes
Solve the equation -6 = -9 – 3x for x. A.-2 B.-1 C.0 D.1

User Sharondio
by
5.3k points

2 Answers

3 votes

Answer:

B. -1

Explanation:

-6 = -9 - 3x

1. get the variable x by itself by adding 9 to both sides

-6 = -9 - 3x

+9 +9

3 = -3x

2. solve for x by dividing by -3 on both sides

3 = -3x

/-3 /-3

3/ -3 = -1

x = -1

1 vote

Answer:

B. -1

Step-by-step explanation:

-6 = -9 - 3x

get the variable x by itself by adding 9 to both sides

-6 = -9 - 3x

+9 +9

3 = -3x

solve for x by dividing by -3 on both sides

3 = -3x

/-3 /-3

3/ -3 = -1

x = -1

User Phschoen
by
5.4k points